Comparison of Diagnostic Accuracy of Microscopy and Flow Cytometry in Evaluating N-Methyl-D-Aspartate Receptor Antibodies in Serum Using a Live Cell-Based Assay - Ramberger, Melanie; Peschl, Patrick; Schanda, Kathrin; Irschick, Regina; Höftberger, Romana; Deisenhammer, Florian; Rostásy, Kevin; Berger, Thomas; Dalmau, Josep; Reindl, Markus (PloS one, 2015)
N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune neurological disease, diagnosed by a specific autoantibody against NMDAR. Antibody testing using commercially available cell-based assays (CBA) or immunohistochemistry on rat brain tissue has proven high specificity and sensitivity. Here we compare an immunofluorescence live CBA to a flow cytometry (FACS) based assay to detect NMDAR antibodies by their binding to the surface of HEK293A cells functionally expressing NMDAR. Both assays were first established using a discovery group of 76 individuals and then validated in a group of 32 patients in a blinded manner. In the CBA, 23 of 23 patients with NMDAR encephalitis were positive for NMDAR antibodies and 0 of 85 controls (32 healthy controls and 53 patients with other neurological diseases), resulting in a sensitivity and specificity of 100% (95% confidence intervals (CI) 85.1-100.0 and 95.7-100.0, respectively). The FACS based assay detected NMDAR antibodies in 20 of 23 patients and in 0 of 85 controls. Therefore, with an equally high specificity (95% CI 95.7-100.0) the sensitivity of the FACS based assay was 87% (95% CI 66.4-97.2). Comparing antibody titers from CBA with delta median fluorescence intensities from FACS showed a high concordance (kappa = 0.943, p<0.0001) and correlation (r = 0.697, p<0.0001). In conclusion, evaluation of the FACS based assay revealed a lower sensitivity and high inter-assay variation, making the CBA a more reliable detection method.